2022
DOI: 10.1111/jvh.13779
|View full text |Cite
|
Sign up to set email alerts
|

The Delta Delta: Gaps in screening and patient assessment for hepatitis D virus infection

Abstract: Hepatitis D virus (HDV) infection is highly prevalent in patients with chronic hepatitis B (CHB). AASLD guidelines recommend a risk-based screening approach. Our aim was to ascertain if the risk-based approach leads to appropriate HDV screening, identify targets to improve screening rates, and study HDV clinical burden. CHB patients screened for HDV from 01/2016 to 12/2021 were identified. Level of training and specialty of providers ordering HDV screening tests were determined. HDV seropositive (HDV+) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 23 publications
(53 reference statements)
1
27
0
Order By: Relevance
“…This is in contrast to standard testing protocols that rely on detection of HBV to trigger HDV testing and, only then, a limited number of HBV patients are tested for evidence of an HDV co-infection. In the United States, multiple studies have reported that less than 20% of HBV patients are tested for HDV[ 6 , 34 , 47 49 ]. Therefore, national testing guidelines, local reporting requirements and compliance in testing HBV patients for HDV may significantly impact the reported cases of HBV and HDV.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to standard testing protocols that rely on detection of HBV to trigger HDV testing and, only then, a limited number of HBV patients are tested for evidence of an HDV co-infection. In the United States, multiple studies have reported that less than 20% of HBV patients are tested for HDV[ 6 , 34 , 47 49 ]. Therefore, national testing guidelines, local reporting requirements and compliance in testing HBV patients for HDV may significantly impact the reported cases of HBV and HDV.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, among patients with anti‐HDV antibody positivity, 40% had detectable HDV RNA. However, because most HDV superinfections in patients with HBV infection progress to chronic HDV infection, and HDV RNA levels decline over time, most patients with HBV infection with anti‐HDV antibody serum positivity could be assumed to have current or resolved HDV chronic infection 24 . Notably, no standardized HDV RNA assays exist 21 ; a negative HBV RNA assay could indicate resolved hepatitis D, low viremia, or a false‐negative test result 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, because most HDV superinfections in patients with HBV infection progress to chronic HDV infection, and HDV RNA levels decline over time, most patients with HBV infection with anti‐HDV antibody serum positivity could be assumed to have current or resolved HDV chronic infection 24 . Notably, no standardized HDV RNA assays exist 21 ; a negative HBV RNA assay could indicate resolved hepatitis D, low viremia, or a false‐negative test result 24 . Additionally, the changes in the FIB‐4 index were similar between patients with anti‐HDV positivity with or without HDV RNA positivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the AASLD guidelines recommend HDV testing only in HBV patients with known risk factors for HDV, including those born in regions with high HDV prevalence, men who have sex with men (MSM), intravenous drug use (IVDU), patients with a history of HCV and HIV, multiple sexual partners, or elevated liver enzymes with limited detectable HBV DNA. The AASLD guidelines may lead to limited HDV testing in patients with HBV who do not present with or have unreported risk factors 7 . For those tested, AASLD recommends testing for anti-HDV antibodies and, subsequently, HDV RNA in patients who are HDV antibody positive (Fig 1) 6 .…”
Section: Introductionmentioning
confidence: 99%